Development of Public Libraries through Public-private Partnership in India: Issues and Challenges - Muralidhar, D.; Koteswara Rao, M. (DESIDOC Journal of Library & Information Technology, 2013)
The paper describes the concept of public-private partnership (PPP) and examines how it is different from ‘privatisation’ concept. It examines the present status of public libraries in India and the need formobilising support for their improvement. The authors stress the need for implementing the National Knowledge Commission recommendation for PPP. The paper highlights the role of the public sector andprivate fi rms in developing public libraries through the PPP model. At the end suggestions were madeon how to implementation the model for the development of public libraries. http://dx.doi.org/10.14429/djlit.33.1.3725